2003
DOI: 10.1021/om020995p
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the Bis(dihydrogen) Complex [RuH2(η2-H2)2(PCy3)2] toward N-Heteroaromatic Compounds. Regioselective Hydrogenation of Acridine to 1,2,3,4,5,6,7,8-Octahydroacridine

Abstract: The reaction of pyridine (Py), pyrrole (Pyr), or acridine with the bis(dihydrogen) complex [RuH2(η 2-H2)2(PCy3)2] (1) produces compounds containing heteroaromatic ([RuH2(η 2-H2)(η 1(N)-C5H5N)(PCy3)2] (2), [RuH(η 5-C4H4N)(PCy3)2]·Pyr (3)) or aromatic rings ([RuH2(η 4-C13H9N)(PCy3)2] (5)) coordinated in η 1(N) (2), η 5 (N,C) (3), or η 4(C,C) (5) modes for Py, Pyr, and acridine, respectively. Complex 3 has been characterized by X-ray crystallography. Its protonation by HBF4 affords the cationic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 58 publications
5
41
0
Order By: Relevance
“…In an attempt to correlate the catalytic performance of comparable precursors with the nature of the metal center, Sánchez-Delgado and Gonzáles have investigated the selective hydrogenation of quinoline to THQ (150 8C, 30 bar H 2 , toluene) by RuCl 2 [77,78], and RuH 2 (g 2 -H 2 ) 2 (PCy 3 ) 2 (TOF quinoline/5,6,7,8-THQ = 2; TOF indole/indoline < 1) [79]. The latter complex also led to saturation of the aromatic ring, which has been proposed to involve the coordination of the substrate through the aromatic ring, in a manner similar to that reported for g 4 -arene complexes (see Scheme 16.4).…”
Section: N-heteroaromaticsmentioning
confidence: 99%
“…In an attempt to correlate the catalytic performance of comparable precursors with the nature of the metal center, Sánchez-Delgado and Gonzáles have investigated the selective hydrogenation of quinoline to THQ (150 8C, 30 bar H 2 , toluene) by RuCl 2 [77,78], and RuH 2 (g 2 -H 2 ) 2 (PCy 3 ) 2 (TOF quinoline/5,6,7,8-THQ = 2; TOF indole/indoline < 1) [79]. The latter complex also led to saturation of the aromatic ring, which has been proposed to involve the coordination of the substrate through the aromatic ring, in a manner similar to that reported for g 4 -arene complexes (see Scheme 16.4).…”
Section: N-heteroaromaticsmentioning
confidence: 99%
“…[7,8] [10,11] and the systems RuCl 2 (NCMe) 4 /Tp and M 2 Cl 2 (COE) 4 /Tp (Tp = tris(pyrazolyl)borate ligands) [12]; in all of cases only the reduction of the heterocyclic ring was observed, obtaining 1,2,3,4-tetrahydroquinoline (THQ) as the product. However, Borowski et al [13] reported the regioselective hydrogenation of the nonheterocyclic ring of Q by using RuH 2 (g 2 -H 2 ) 2 (PCy 3 ) 2 as the precatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…In all these cases only the reduction of the heterocyclic ring was observed. Recently, Borowski et al [9] reported the regioselective hydrogenation of the non-heterocyclic rings of quinoline, isoquinoline and acridine by using [RuH 2 (g 2 )H 2 ) 2 (PCy 3 ) 2 ] (Cy = cyclohexyl) as the precatalyst. So far the used precatalysts are based on monodentade phosphines, although systems containing tris(pyrazolyl)borate ligands have been reported in the literature [10].…”
Section: Introductionmentioning
confidence: 99%